Resistin Gene Expression in Human Adipocytes Is Not Related to Insulin Resistance - Jürgen Janke; Stefan Engeli; Kerstin Gorzelniak; Friedrich C. Luft; Arya M. Sharma (2002)
Abstract Objectives: Obesity is an important risk factor for the development of insulin resistance and type 2 diabetes. Recently, a newly described circulating hormone resistin, which is expressed primarily in adipocytes, has been shown to antagonize insulin action in mice. Resistin, therefore, has been suggested to play a role in the pathogenesis of insulin resistance. Research Methods and Procedures: We studied the expression of the resistin gene in primary cultured human adipocytes and preadipocytes. We also examined resistin gene expression in subcutaneous abdominal adipocytes in women ( n = 24) over a wide range of body weight and insulin sensitivity. Results: Whereas resistin gene expression was barely detectable in mature adipocytes, it was highly expressed in preadipocytes. Adipogenic differentiation of preadipocytes was associated with a time‐dependent down‐regulation of resistin gene expression. There was no relationship between body weight, insulin sensitivity, or other metabolic parameters and adipocyte resistin gene expression in the clinical study. Discussion: Together these findings do not support an important role of adipose‐tissue resistin gene expression in human insulin resistance.